MICROCALORIMETRIC ANALYSIS OF THE ADSORPTION OF CARBON OXYSULFIDE MOLECULES ON NAX ZEOLITE (Scientific journal of the Fergana State University, 2025)
The article provides information on the adsorption properties of synthetic zeolites of type X, their ion-molecular mechanisms, as well as research studies on the adsorption of sulfur-containing compounds conducted by foreign and local scientists. The methodology for determining the complete thermodynamic characteristics of the adsorption of carbon oxysulfide molecules on NaX zeolite by the volumetric method using a high-vacuum microcalorimetric setup is presented. It is also proven that the differential heat of adsorption of COS molecules on NaX zeolite has a stepwise nature, with the ion-molecular complexes (COS)n/Men+ formed at each step corresponding to stoichiometric dimensions [1-2]. The adsorption isotherms of carbon oxysulfide molecules on NaX-type zeolites were calculated based on the mathematical equations of the volume saturation theory of micropores.